In-depth analysis of deep learning architectures for brain tumor classification in MRI scans - Haque, Hossain MD. Hasibul; Apon, MD. Sayeed Arefin; Chowdhury, Dhrubo Rashid; Imtiaz, Shahriar Islam; Mahi, Nishat Tasnim (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.